Review of Thoracic (Chest) Trauma 2002 AD at Shree Birendra Hospital - Rajbhandari, Gambhir Lal (Medical Journal of Shree Birendra Hospital, 2002)
Review  of Thoracic (Chest) Trauma 2002 AD at Shree Birendra Hospital